2022
DOI: 10.3389/fpubh.2022.933005
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practices Toward Tuberculosis Among Hospital Outpatients in Kabul, Afghanistan

Abstract: BackgroundTuberculosis (TB) is a high-burden respiratory infectious disease. There was a sharp decline in the number of confirmed TB cases during the pandemic; this is likely to be influenced by the COVID-19 pandemic response, with under-reporting due to resource diversion. There are typically 13,000 tuberculosis-associated deaths in Afghanistan annually, with significant problems posed by drug-resistant TB.MethodA cross-sectional descriptive study was conducted in Afghanistan on Kabul residents who visited th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 12 publications
1
5
2
Order By: Relevance
“…In contrast to a study conducted in Ethiopia, which found that 46% of respondents had a low level of knowledge about TB [12], the current study found that total knowledge about TB was 64% lower. The current finding, however, was superior to a study conducted in Afghanistan [13], where nearly 88% of individuals had a good awareness of TB. The latter study's score was substantially correlated with attitude assessment, age, and gender.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to a study conducted in Ethiopia, which found that 46% of respondents had a low level of knowledge about TB [12], the current study found that total knowledge about TB was 64% lower. The current finding, however, was superior to a study conducted in Afghanistan [13], where nearly 88% of individuals had a good awareness of TB. The latter study's score was substantially correlated with attitude assessment, age, and gender.…”
Section: Discussioncontrasting
confidence: 99%
“…This result is consistent with that of a different study carried out in Tepi General Hospital in Ethiopia, where the majority of participants (70%) said that the spread of the illness could not be stopped, while 92 (22.4%) said that covering the mouth and nose while coughing or sneezing could help stop the spread [18]. The results, however, contrast with those from Kabul, where 98 percent of participants indicated that TB transmission could be prevented [13]. Cough was the primary symptom mentioned by the majority of individuals (90.4%), followed by fever (80.8%) and loss of appetite (62.3%).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A hospital review of extrapulmonary TB cases in Kabul found a majority were women, indicating potential gender differences [ 13 ]. Studies in Kabul revealed knowledge gaps and stigmatizing attitudes about TB among Afghans in Pakistan [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%